Impact of environmental interventions based on social programs on physical activity levels: A systematic review - Hernández, Edgar D.; Cobo, Elisa A.; Cahalin, Lawrence P.; Seron, Pamela (Frontiers in Public Health, 2023)
Background The design of social programs at the environmental level such as in schools, parks, bicycle paths, or workspaces generates changes in the behavior of individuals and modifies lifestyles by increasing physical activity (PA) levels. Objective To determine the effectiveness of environmental interventions based on social programs by changing the population's level of PA. Methodology Natural experiment studies that involved environmental intervention programs at a social level were included. The primary outcome was PA levels with consideration of both objective and subjective measurements. An electronic search was carried out in Medline/Pubmed, SCIENCE DIRECT, WEB OF SCIENCE, and CINAHL databases up to January 2022 with two reviewers screening titles and abstracts and selecting studies for full-text reading. Two reviewers also acquired relevant data and evaluated study quality using the ROBINS I tool. A qualitative analysis was performed. Results Three thousand eight hundred and sixty-five articles were found in the 4 consulted databases. After eliminating duplication (200), two reviewers screened 3,665 titles and abstracts and excluded 3,566 that did not meet the inclusion criteria, leaving 99 articles to be read in full text. The 99 full texts were reviewed of which 24 papers met the eligibility criteria. All were natural experiments published between 2011 and 2020 and all evaluated environmental social programs revealing that social programs at the environmental level promoted PA in various populations at the community level worldwide. Conclusion The 24 reviewed studies suggest innovative proposals for social programs that seek to increase PA and promote healthy lifestyles related to public activity policies developed in the countries in which they were generated. Environmental social programs can positively impact PA levels among children and adults. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=229718, identifier: CRD42021229718.